A5.6 Anti-Carbamylated Protein Antibodies are Present in Mice with Collagen induced Arthritis. (25th February 2013) - Stoop, Jeroen; Liu, Bisheng; Shi, Jing; Jansen, Diahann; Trouw, Leendert; Toes, Rene
Abstract : Objective: Antibodies against citrullinated proteins (ACPA) are a characteristic of rheumatoid arthritis (RA). Carbamylation is a different type of post translational modification, where a Lysine amino acid is converted into a homocitrullin. Recently we identified antibodies binding to carbamylated proteins (anti-CarP) in a subgroup of RA patients. In ACPA negative RA patients anti-CarP antibodies associate with joint damage. The Aim of this study was to determine whether these anti-CarP antibodies are present in animal models of arthritis. Methods: Collagen induced arthritis (CIA) was induced in DBA/1 (n = 29) and C57Bl/6 (n = 20) mice by immunisation with type II collagen in CFA. Arthritis severity was monitored using a clinical scoring system. Non-immunised animals (n = 9) served as negative controls. After disease onset serum was harvested and antibody levels were determined by ELISA. The specificity of our anti-CarP. ELISA was validated using dotblots. Results: Whereas no anti-CarP antibodies could be detected in non-immunised DBA/1 mice, anti-CarP total Ig was present in 93% of the arthritic mice. Of those mice 39% had IgG1 and 79% had IgG2a anti-CarP antibodies. Antibodies to citrullinated proteins could not be detected. The levels of mouse collagen-specific IgG2a correlated with the clinical score. However, the levels of the different anti-CarP isotypes did not. Around 60% of the immunised C56Bl/6 mice developed arthritis. Anti-CarP IgG2c could be detected in 55% of those mice and could not be detected in the mice that did not get CIA. Anti-CarP IgG1 was detected in 28% of the arthritic mice. Interestingly, mouse collagen specific IgG2c antibodies were detected in 100% of the immunised C57Bl/6 mice. Dotblot analysis, using carbamylated and non-modified proteins confirmed the ELISA results regarding the specificity of the antibodies for homocitrulline containing proteins. Conclusions: Mice with CIA have antibodies to carbamylated proteins and their presence associated with disease development. All immunised mice have anti-mouse CII antibodies, indicating that the presence of anti-CarP antibodies could be a disease specific marker for arthritis in mice. Further studies will be required to determine the role of anti-CarP in the pathogenesis of arthritis.